2019
DOI: 10.1021/acsami.9b14744
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Fatigue Behavior and Its Influence on the Thermoelectric Properties of p-Type Bi0.5Sb1.5Te3 Alloys

Abstract: BiSbTe alloy is one of the most important thermoelectric materials that has been commercialized for large-scale applications in waste heat recovery and spot cooling. However, its practical application often involves complicated service conditions, such as substantial dynamic vibrational stresses as well as long-term exposure to the large thermal gradient that usually generates high thermal stress. Thus, it is of vital importance to investigate the mechanical response and the evolution of microstructure and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The recent study has reported the compressive fatigue behavior of p-type Bi 0.5 Sb 1.5 Te 3 material fabricated by the MS-PAS method. 105 The fatigue life increases significantly up to 9 × 10 5 when the stress ratio decreases to 60% (i.e., equals to 68 MPa), approaching the fatigue limit (10 6 ), as shown in Figure 10a. Thus, the fatigue strength limit of MS-PAS-prepared Bi 0.5 Sb 1.5 Te 3 material is nearly 68 MPa.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 89%
See 2 more Smart Citations
“…The recent study has reported the compressive fatigue behavior of p-type Bi 0.5 Sb 1.5 Te 3 material fabricated by the MS-PAS method. 105 The fatigue life increases significantly up to 9 × 10 5 when the stress ratio decreases to 60% (i.e., equals to 68 MPa), approaching the fatigue limit (10 6 ), as shown in Figure 10a. Thus, the fatigue strength limit of MS-PAS-prepared Bi 0.5 Sb 1.5 Te 3 material is nearly 68 MPa.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 89%
“…These external fields usually bring about fatigue or creep phenomena which will inevitably degrade both TE and mechanical performances. The recent study has reported the compressive fatigue behavior of p-type Bi 0.5 Sb 1.5 Te 3 material fabricated by the MS-PAS method . The fatigue life increases significantly up to 9 × 10 5 when the stress ratio decreases to 60% (i.e., equals to 68 MPa), approaching the fatigue limit (10 6 ), as shown in Figure a.…”
Section: Mechanical Response Of Bi2te3-based Materialsmentioning
confidence: 92%
See 1 more Smart Citation
“…To date, most research was focused on enhancing the thermoelectric performance of Cu 2 Se materials. It is noteworthy that during the long-term service, thermoelectric materials are exposed to thermal shock, thermal cycling, and mechanical vibration, which require materials with robust mechanical properties. However, the existing literature was focused on some specific aspects of the mechanical performance, and the systematic study of the mechanical behavior of Cu 2 Se materials was rarely reported. Moreover, for large-scale application, excellent thermal stability is also of equal significance as excellent thermoelectric performance. At high temperatures, the composition and microstructure vary with duration time due to the intensified interdiffusion of atoms, and especially for Cu 2 Se, the long-range migration of liquid-like Cu + would accelerate thermal fatigue, deteriorating the thermoelectric performance and further causing the failure of thermoelectric modules.…”
Section: Introductionmentioning
confidence: 99%
“…These works indicated that reducing lattice thermal conductivity by multi-scale defects is indeed a very promising scheme to significantly improve the TE properties of Bi 2 Te 3 -based sintered materials. It is also found that many of obtained κ tot values are still at some high level, and there is still room for further improvement of the TE performance. Additionally, some synthetic methods may need some simplifications to meet the requirement of large-scale applications.…”
Section: Introductionmentioning
confidence: 99%